2002
DOI: 10.1074/jbc.m200909200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Neuroglycan C, a Brain-specific Transmembrane Chondroitin Sulfate Proteoglycan, and Its Localization in the Lipid Rafts

Abstract: Neuroglycan C (NGC) is a brain-specific transmembrane chondroitin sulfate proteoglycan. In the present study, we examined whether NGC could be phosphorylated in neural cells. On metabolic labeling of cultured cerebral cortical cells from the rat fetus with 32 P i , serine residues in NGC were radiolabeled. Some NGC became detectable in the raft fraction from the rat cerebrum, a signaling microdomain of the plasma membrane, with cerebral development. NGC from the non-raft fraction, not the raft fraction, could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Interestingly, both syndecans and chemokine receptors enhance HIV-1 transcytosis through PGECs. Previous studies showed that syndecans are associated with lipid rafts (22,33,54,56,65) and form complexes with CXCR4 and CCR5 on the cell surface (54). This suggests the possibility that syndecans and chemokine receptors are in close proximity on the surface of PGECs and that they cooperate for successful cell-free virus transcytosis.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, both syndecans and chemokine receptors enhance HIV-1 transcytosis through PGECs. Previous studies showed that syndecans are associated with lipid rafts (22,33,54,56,65) and form complexes with CXCR4 and CCR5 on the cell surface (54). This suggests the possibility that syndecans and chemokine receptors are in close proximity on the surface of PGECs and that they cooperate for successful cell-free virus transcytosis.…”
Section: Discussionmentioning
confidence: 92%
“…They postulated that proteoglycans facilitate HIV-1 entry into BMECs, either by rescuing HIV-1 from abortive endocytosis or by directing HIV-1 particles into safe transcytosis routes (8). Given that we and others showed that gp120 serves as the main ligand for HSPGs (15,54,72,96), it is difficult to imagine that HSPGs and CSPGs abundantly expressed on BMECs would not, at least in part, contribute to the initial attachment of HIV-1 to BMECs. Nevertheless, these apparent discrepancies may arise from the cell origin or cell culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, it can be concluded that a significant part of NGCs exist in a non-CSPG form. The 220-kDa band may be a dimer of the NGC core protein, because NGC tends to polymerize during preparation or enzymatic digestion (35). The 110-kDa band may be an immature form of NGC with less post-translational modification or a degradation product.…”
Section: Localization Of Cspgs To the Niche Of Neural Stem Cells-mentioning
confidence: 99%